Method for improving the interface binding of electrolyte and cathode based on femtosecond laser surface groove structure

By etching grooves on the electrolyte surface and combining them with screen printing and high-temperature sintering, the problem of poor bonding between the electrolyte and the cathode interface was solved, thereby improving the bonding strength and reducing the polarization resistance.

CN117410535BActive Publication Date: 2026-11-06HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311358224.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2026-11-06
Estimated Expiration
2043-10-19

AI Technical Summary

Technical Problem

In existing technologies, the electrolyte-cathode interface has poor bonding, which leads to easy cracking, delamination, and high polarization resistance, thus affecting the full utilization of proton conductivity.

Method used

A femtosecond laser is used to etch a trench structure on the electrolyte surface, which is then combined with screen printing and high-temperature sintering to prepare the bond between the electrolyte and the cathode.

Benefits of technology

It improves the bonding strength between the electrolyte and the cathode, reduces the polarization resistance, increases the contact area, and improves the interface connection effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117410535B_ABST
    Figure CN117410535B_ABST
Patent Text Reader

Abstract

This invention addresses the problem of poor electrolyte-cathode interface bonding in current SOFCs by using a femtosecond laser to create surface trench structures. The method involves: 1) etching the surface of the BZCYYb ceramic to be bonded using a femtosecond laser to form trench structures; 2) transferring the initial cathode powder to a muffle furnace, calcining it, and then adding a binder to obtain a battery cathode slurry; 3) applying the battery cathode slurry onto the grooved BZCYYb electrolyte using screen printing; and 4) sintering the bonding. This invention utilizes femtosecond laser grooving, which removes inactive surfaces, increases the contact area, and incorporates a mechanical interlocking effect. Furthermore, the resulting three-dimensional porous surface structure exposes micron-sized particles, promoting the sintering process and improving interfacial bonding strength, while reducing polarization resistance by 54%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for improving the interface bonding between the electrolyte and the cathode through femtosecond laser surface junctions. Background Technology

[0002] With energy shortages and environmental degradation such as air pollution and greenhouse gases caused by the burning of large amounts of fossil fuels, efficient and low-cost technologies for the acquisition and utilization of green hydrogen energy are of profound significance. Because fuel cells can directly convert the chemical energy in hydrogen into electrical energy, they have become one of the most promising energy conversion technologies. Among them, solid oxide fuel cells (SOFCs) have attracted widespread attention due to their outstanding advantages such as high power density, light weight, low cost, and high flexibility.

[0003] SOFCs can be classified into oxygen-ion-conducting and proton-conducting types based on their conductivity. Older generation solid oxide fuel cells, represented by YSZ, typically operate effectively only at high temperatures of 700–1000°C due to their oxygen-ion-conducting nature. In contrast, proton-conducting PCFCs have a low activation energy, allowing them to operate at lower temperatures and exhibit wider environmental adaptability.

[0004] In the fabrication of PCFC single cells, the electrolyte needs to be sintered and bonded to the cathode, a technology that has always been a bottleneck in single-cell fabrication. Currently, the commonly used process involves screen-printing the cathode onto the electrolyte and then achieving the bond through high-temperature sintering. However, because the co-firing of the electrolyte and anode in the previous step requires a high temperature, resulting in a bright and inactive annealed surface, the sintered bond at this point suffers from weak bonding and few bonding sites. This leads to easy cracking, delamination, and other forms of degradation at the interface, as well as a large polarization resistance. Based on these factors, the theoretical proton / ionic conductivity of the electrolyte cannot be fully realized.

[0005] Currently, common methods for improving the interface between the electrolyte and cathode include mechanical polishing, pulsed laser deposition (PLD) of the cathode layer, and acid pickling. Mechanical polishing with sandpaper can easily damage the electrolyte, leading to gas leakage. PLD technology pre-fabricates the cathode layer on the electrolyte surface, significantly improving the interface. However, it typically requires a high vacuum or inert atmosphere, limiting the range of available materials and suffering from low efficiency and complex operation. Acid pickling removes non-reactive surfaces, increases surface roughness, thereby promoting sintering, reducing contact resistance, and improving electrical performance. It is currently the simplest and most effective method, but its parameter stability is poor.

[0006] In summary, surface treatment of the electrolyte is expected to further improve connectivity. However, considering that the electrolyte thickness is typically less than 20 μm, conventional processing methods can easily disrupt its integrity. Summary of the Invention

[0007] This invention aims to address the problem of poor bonding between the electrolyte and cathode interface in current SOFCs by providing a method based on femtosecond laser surface trench structure to improve the bonding between the electrolyte and cathode interface.

[0008] The present invention provides a method for improving the bonding between the electrolyte and cathode interface based on femtosecond laser surface trench structures, implemented according to the following steps:

[0009] I. Electrolyte preparation:

[0010] The surface of the BZCYYb ceramic to be joined is etched using a femtosecond laser to form a groove structure on the surface of the BZCYYb ceramic. Then, it is ultrasonically cleaned with anhydrous ethanol or acetone and dried to obtain the grooved BZCYYb electrolyte.

[0011] II. Cathode Preparation:

[0012] a. Dissolve the nitrates of Pr, Co, and Ni in water, then add glycine and mix. Adjust the pH of the system to 3-4, then heat at 400℃ to evaporate the solvent to form a gel. Transfer the gel to an evaporating dish and heat for self-propagating combustion to obtain the initial powder.

[0013] b. Transfer the initial powder to a muffle furnace and calcine it at a temperature of 800-1000℃ to form a phase. Grind the formed powder evenly and add a binder to prepare the battery cathode slurry.

[0014] III. Screen Printing:

[0015] The battery cathode paste is coated onto the grooved BZCYYb electrolyte using a screen printing process to obtain an electrolyte with cathode paste.

[0016] IV. Sintering connection:

[0017] The electrolyte containing the cathode slurry is placed in a muffle furnace and sintered at a temperature of 1000–1200°C in an air atmosphere to obtain the battery cathode, thus completing the interface bonding between the electrolyte and the cathode.

[0018] This invention employs a femtosecond laser with a repetition frequency of 1 kHz at a power of 3 mw to 8 mw and a scanning speed of 4 mm / s to fabricate trench structures on the surface of the BZCYYb electrolyte to be connected, preparing I-shaped (straight-line) or grid-shaped trench structures. After screen printing a PNC55 cathode, the connection between the electrolyte and the cathode is achieved by holding the cathode at 1150℃ in air for 4 hours.

[0019] The method for improving the interface bonding between the electrolyte and cathode based on the femtosecond laser surface trench structure of this invention has the following beneficial effects:

[0020] I. This invention uses femtosecond lasers to process the surface of electrolytes. Femtosecond lasers have the characteristics of high peak power and small heat-affected zone, and can perform micron-level precision surface processing.

[0021] Second, this invention employs femtosecond laser grooving, which not only removes inactive surfaces but also increases the contact area and incorporates a mechanical interlocking effect. Simultaneously, the resulting three-dimensional porous surface structure exposes micron-sized particles that promote the sintering process, thereby improving interfacial bonding strength and reducing polarization resistance by 54%.

[0022] Third, this invention uses femtosecond laser surface processing, which has controllable process parameters, good stability, simple process, and easy operation. Attached Figure Description

[0023] Figure 1 This is a SEM image of the electrolyte surface before processing in the example;

[0024] Figure 2 This is a roughness test image of the electrolyte surface before processing in the embodiment;

[0025] Figure 3 This is an SEM image of the processed electrolyte surface in the example;

[0026] Figure 4 This is a roughness test diagram of the electrolyte surface after processing in the embodiment;

[0027] Figure 5 The following are XRD patterns of the electrolyte surface before and after femtosecond laser processing in the embodiment, where A represents the electrolyte processed by femtosecond laser and B represents the electrolyte without laser processing;

[0028] Figure 6 The above are XPS images of the electrolyte surface before and after femtosecond laser processing in the example.

[0029] Figure 7 The image shown is a SEM image of the electrolyte-cathode interface before and after femtosecond laser processing in the example.

[0030] Figure 8 The EIS impedance spectra of symmetrical cells processed by different femtosecond lasers are shown in the examples. Detailed Implementation

[0031] Specific Implementation Method 1: This implementation method, based on femtosecond laser surface trench structure to improve the bonding between the electrolyte and cathode interface, is carried out according to the following steps:

[0032] I. Electrolyte preparation:

[0033] The surface of the BZCYYb ceramic to be joined is etched using a femtosecond laser to form a groove structure on the surface of the BZCYYb ceramic. Then, it is ultrasonically cleaned with anhydrous ethanol or acetone and dried to obtain the grooved BZCYYb electrolyte.

[0034] II. Cathode Preparation:

[0035] a. Dissolve the nitrates of Pr, Co, and Ni in water, then add glycine and mix. Adjust the pH of the system to 3-4, then heat at 400℃ to evaporate the solvent to form a gel. Transfer the gel to an evaporating dish and heat for self-propagating combustion to obtain the initial powder.

[0036] b. Transfer the initial powder to a muffle furnace and calcine it at a temperature of 800-1000℃ to form a phase. Grind the formed powder evenly and add a binder to prepare the battery cathode slurry.

[0037] III. Screen Printing:

[0038] The battery cathode paste is coated onto the grooved BZCYYb electrolyte using a screen printing process to obtain an electrolyte with cathode paste.

[0039] IV. Sintering connection:

[0040] The electrolyte containing the cathode slurry is placed in a muffle furnace and sintered at a temperature of 1000–1200°C in an air atmosphere to obtain the battery cathode, thus completing the interface bonding between the electrolyte and the cathode.

[0041] In this embodiment, the electrolyte can also be a proton conductor such as BZCYYb, BZCY, or an oxygen ion conductor YSZ.

[0042] Femtosecond lasers have the characteristics of high peak power and small heat-affected zone, and can perform micron-level surface processing. Therefore, this embodiment uses femtosecond lasers to design the surface structure of the electrolyte, thereby achieving the effects of removing non-active surfaces, mechanical interlocking, and increasing the contact area, thus improving the connection between the two.

[0043] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that in step one, a femtosecond laser with a repetition frequency of 1kHz is used at a power of 3mw to 8mw and a scanning speed of 1 to 4mm / s to be connected to etch the BZCYYb ceramic surface.

[0044] Specific Implementation Method 3: This implementation method differs from Specific Implementation Method 2 in that in step one, a femtosecond laser with a repetition frequency of 1kHz is used at a power of 8mw and a scanning speed of 4mm / s to etch the BZCYYb ceramic surface to be joined.

[0045] According to research, this embodiment shows that as the power of the femtosecond laser increases and the scanning speed decreases, both the depth and width of the etched trenches increase.

[0046] Specific Implementation Method Four: This implementation method differs from one of the specific implementation methods one to three in that the trench structure in step one is I-shaped or grid-shaped.

[0047] Specific Implementation Method 5: This implementation method differs from Specific Implementation Methods 1 to 4 in that the width of the etched grooves in step 1 is 3μm to 25μm.

[0048] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that the surface roughness of the BZCYYb electrolyte after grooving in Step One is 0.24 to 0.3 SRa.

[0049] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One to Six in that the molar ratio of Pr nitrate, Co nitrate, and Ni nitrate in step two is (1.55~2.5):(0.5~1.5):(0.5~1.5).

[0050] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods One to Seven in that step b involves calcination at a temperature of 800–1000°C for 2–4 hours.

[0051] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that the adhesive mentioned in step b is PVB (polyvinyl butyral) with a mass fraction of 5%.

[0052] Specific Implementation Method 10: This implementation method differs from Specific Implementation Methods 1 to 9 in that the coating thickness of the battery cathode slurry in step 3 is 50-100 μm.

[0053] Specific Implementation Method Eleven: This implementation method differs from Specific Implementation Methods One through Ten in that in step four, the furnace temperature is raised to 1000-1200℃ at a heating rate of 5℃ / min for sintering treatment for 3-5 hours.

[0054] Example: This example demonstrates a method for improving the interface between the electrolyte and cathode based on femtosecond laser surface trench structures, implemented according to the following steps:

[0055] I. Electrolyte preparation:

[0056] A femtosecond laser with a frequency of 1 kHz, a power of 8 mw, and a scanning speed of 4 mm / s was used to etch the surface of the BZCYYb ceramic to be joined along one direction. The sample stage was rotated 90° and the same femtosecond laser process was used again to etch, forming a grid-shaped groove structure on the surface of the BZCYYb ceramic. The spacing between two adjacent grooves was 15 μm. Then, the surface was ultrasonically cleaned with anhydrous ethanol for 5 min and dried to obtain the grooved BZCYYb electrolyte.

[0057] II. Cathode Preparation:

[0058] a. Dissolve 0.02 mol praseodymium nitrate, 0.01 mol cobalt nitrate and 0.01 mol nickel nitrate in 100 mL of water, then add glycine and mix. Adjust the pH of the system to 3, then heat at 400 °C to evaporate the solvent to form a gel. Transfer the gel to an evaporating dish and heat it for self-propagating combustion to obtain the initial powder.

[0059] b. Transfer the initial powder to a muffle furnace and calcine it at 900℃ for 4 hours to form a phase. Grind the formed powder evenly and add a binder to prepare the battery cathode slurry.

[0060] III. Screen Printing:

[0061] The battery cathode paste was coated onto the grooved BZCYYb electrolyte using a screen printing process to obtain an electrolyte with cathode paste, and the coating thickness was 80μm.

[0062] IV. Sintering connection:

[0063] The electrolyte containing the cathode slurry is placed in a muffle furnace, and the furnace temperature is raised from room temperature to 1150°C at a heating rate of 5°C / min under air atmosphere. The temperature is held for 4 hours to obtain the battery cathode, thus completing the interface bonding between the electrolyte and the cathode.

[0064] Figures 1-4 The images show typical surface morphology of the electrolyte before and after femtosecond laser processing. After femtosecond laser processing, a continuous groove structure was obtained, and the surface roughness increased from 0.149 SRa to 0.259 SRa. Unexpectedly, a micron-scale three-dimensional porous structure was also obtained, increasing the exposed surface area by over 98%, which is beneficial for improving the driving force for the sintering connection between the electrolyte and the cathode.

[0065] Figure 5 The images show the XRD patterns of the electrolyte surface before and after femtosecond laser processing. Figure 6 The XPS images of the electrolyte surface before and after femtosecond laser processing show that the heat input of femtosecond laser processing is extremely small and does not change the phase composition and chemical valence state of the electrolyte.

[0066] Figure 8The EIS impedance spectra of symmetrical cells (electrolyte coated with cathodes on both sides) of different samples were obtained at 550℃ in air. It can be seen that the polarization resistance of the sample obtained in Example 1 is 3.65 Ω·cm. 2 Reduced to 1.68 Ω·cm 2 This represents a 54% decrease.

[0067] Example 2: This example differs from Example 1 in that the laser power in step 1 is 3mw, and a grid-shaped groove structure is formed on the surface of BZCYYb ceramic using femtosecond laser technology.

[0068] Example 3: This example differs from Example 1 in that the laser power in step 1 is 3mw, and an I-shaped groove structure is formed on the surface of BZCYYb ceramic using femtosecond laser technology.

[0069] according to Figure 8 It can be seen that the sample with well-shaped grooves processed in Example 1 with a laser power of 8mw and a scanning speed of 4mm / s has the best effect, and the polarization resistance is reduced from 3.65Ω·cm. 2 Reduced to 1.68 Ω·cm 2 This represents a 54% reduction. Compared to a laser power of 3mW, a laser power of 8mW results in a wider and deeper trench, exposing more surface area and achieving a stronger surface roughening effect. Furthermore, the grid pattern offers superior performance compared to the I-shaped pattern.

Claims

1. A method for improving the bonding between the electrolyte and cathode interface based on femtosecond laser surface trench structure, characterized in that... The method for improving the bonding between the electrolyte and the cathode interface is implemented according to the following steps: I. Electrolyte preparation: The surface of the BZCYYb ceramic to be joined is etched using a femtosecond laser to form a groove structure on the surface of the BZCYYb ceramic. Then, it is ultrasonically cleaned with anhydrous ethanol or acetone and dried to obtain the grooved BZCYYb electrolyte. II. Cathode Preparation: a. Dissolve the nitrates of Pr, Co, and Ni in water, then add glycine and mix. Adjust the pH of the system to 3-4, then heat at 400℃ to evaporate the solvent to form a gel. Transfer the gel to an evaporating dish and heat for self-propagating combustion to obtain the initial powder. b. Transfer the initial powder to a muffle furnace and calcine it at a temperature of 800~1000℃ to form a phase. Grind the formed powder evenly and add a binder to prepare the battery cathode slurry. III. Screen Printing: The battery cathode paste is coated onto the grooved BZCYYb electrolyte using a screen printing process to obtain an electrolyte with cathode paste. IV. Sintering connection: The electrolyte containing the cathode slurry is placed in a muffle furnace and sintered at a temperature of 1000~1200 ℃ in an air atmosphere to obtain the battery cathode, thus completing the interface bonding between the electrolyte and the cathode.

2. The method for improving the interface bonding between the electrolyte and cathode based on a femtosecond laser surface trench structure according to claim 1, characterized in that... In step one, a femtosecond laser with a repetition frequency of 1 kHz is used to etch the BZCYYb ceramic surface to be joined at a scanning speed of 1-4 mm / s with a power of 3 mw to 8 mw.

3. The method for improving the interface bonding between the electrolyte and cathode based on a femtosecond laser surface trench structure according to claim 2, characterized in that... In step one, a femtosecond laser with a repetition frequency of 1 kHz is used at a power of 8 mw and a scanning speed of 4 mm / s to etch the BZCYYb ceramic surface to be joined.

4. The method for improving the interface bonding between the electrolyte and cathode based on a femtosecond laser surface trench structure according to claim 1, characterized in that... In step one, the trench structure is either straight or grid-shaped.

5. The method for improving the interface bonding between the electrolyte and cathode based on a femtosecond laser surface trench structure according to claim 1, characterized in that... The width of the etched trenches in step one is 3μm~25μm.

6. The method for improving the electrolyte-cathode interface bonding based on femtosecond laser surface trench structure according to claim 1, characterized in that... In step b, the food is calcined at 800-1000℃ for 2-4 hours.

7. The method for improving the interface bonding between the electrolyte and cathode based on a femtosecond laser surface trench structure according to claim 1, characterized in that... In step three, the coating thickness of the battery cathode slurry is 50~100 μm.

8. The method for improving the interface bonding between the electrolyte and cathode based on a femtosecond laser surface trench structure according to claim 1, characterized in that... In step four, the furnace temperature is raised to 1000~1200 ℃ at a heating rate of 5 ℃ / min for sintering treatment for 3~5 h.